When the judge met P: the rules of engagement in the Court of Protection and the parallel universe of children meeting judges in the Family Court. (26th March 2019) - Case, Paula
Abstract: The importance of the subjects of litigation being able to tell their story directly to the decision maker is widely recognised as offering therapeutic benefits to all involved in the decision-making process. The Court of Protection makes life changing decisions for individuals on health and welfare matters, and it is clearly critical that the person at the centre of those proceedings (known as 'P') is given the opportunity for 'direct engagement' with the judge deciding their case. This paper interrogates the under-explored domain of the prevalence and forms in which 'P' has engaged directly with the judge (particularly by meeting with the judge without giving formal evidence) with the aid of a database of over 200 'health and welfare' judgments. An integrated approach is adopted, drawing from these judgments, but also cross-referencing the far more advanced literature and case law on children meeting judges in the Family Court to explore some of the issues. This paper finds that the transplantation of practices from the Family Court to the Court of Protection has been problematic, has sometimes obscured P's direct contact with the judge in their own case, and jars with recent moves in the Court of Protection towards modelling empathetic judging and 'standing in P's shoes'.